Review of Volume 10(3) of the Journal of Studies in International Education - Natasha Jankowski (The Evaluation Center at Western Michigan University, 2007)
The following is a summary of Volume 10(3) of the Journal of Studies in International Education (2006). This volume celebrates the 10th anniversary of the Journal, as well the 10th anniversary of the Center for International Higher Education based in Boston College. The Journal of Studies in International Education has been received international awards from the Association of International Education Administrators and recognition from the Association of International Educators.